2017
DOI: 10.1186/s13054-017-1626-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of clinically available renal biomarkers in critically ill adults: a prospective multicenter observational study

Abstract: BackgroundAlthough serum cystatin C (sCysC), urinary N-acetyl-β-d-glucosaminidase (uNAG), and urinary albumin/creatinine ratio (uACR) are clinically available, their optimal combination for acute kidney injury (AKI) detection and prognosis prediction remains unclear. We aimed to assess the discriminative abilities of these biomarkers and their possible combinations for AKI detection and intensive care unit (ICU) mortality prediction in critically ill adults.MethodsA multicenter, prospective observational study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 49 publications
3
54
0
Order By: Relevance
“…87 In a recent large prospective observational study performed in critically ill adult intensive care unit (ICU) patients, urine NAG levels alone allowed weak to moderate prediction of AKI, severe AKI, and ICU mortality (AUCs, 0.65, 0.71, and 0.79, respectively). 88 α-1-microglobulin (A1M) is a 27-kDa plasma protein produced by the liver. It has an immunoregulatory role and is considered to be an anti-oxidant that can scavenge pro-oxidant heme groups.…”
Section: Q18mentioning
confidence: 99%
“…87 In a recent large prospective observational study performed in critically ill adult intensive care unit (ICU) patients, urine NAG levels alone allowed weak to moderate prediction of AKI, severe AKI, and ICU mortality (AUCs, 0.65, 0.71, and 0.79, respectively). 88 α-1-microglobulin (A1M) is a 27-kDa plasma protein produced by the liver. It has an immunoregulatory role and is considered to be an anti-oxidant that can scavenge pro-oxidant heme groups.…”
Section: Q18mentioning
confidence: 99%
“…The reason for this result may be that indicators with different characteristics have different sensitivities and specificities, and a reasonable combination between them can improve the diagnostic performance. This shared similar mechanism with Deng's research [30], in which the investigator combined a panel of a functional marker (sCysC) and a tubular injury marker (uNAG) to predict outcomes in patients with severe AKI, demonstrating superior discriminating performance compared to sCysC and uNAG alone.…”
Section: Discussionmentioning
confidence: 59%
“…Here we have found for the first time that higher plasma cystatin C concentrations measured early in the course of ARDS are associated with higher mortality and that this association persists after adjustment for AKI defined by creatininebased criteria. Earlier studies reported that elevated cystatin C is associated with higher mortality in heterogenous cohorts of critically-ill patients (5,7,8), but prior to this study, this finding had not been validated in a large cohort of patients with ARDS. Additionally, to the best of our knowledge, this is the first study to test the association of cystatin C and mortality among critically ill patients cared for in North America.…”
Section: Discussionmentioning
confidence: 61%
“…Furthermore, plasma cystatin C measurements are clinically available in many institutions. Elevated cystatin C is associated with higher mortality in heterogenous cohorts of critically-ill patients (5,7,8), but this finding has not been studied in a large cohort of patients with ARDS.…”
mentioning
confidence: 99%